THU0679 Can the use of new technologies improve the use of patient reported outcomes (PROS) and patient participation in a national registry?. (15th June 2017) - Cunha-Miranda, L; Santos, H; Barcelos, F; Madeira, N; Fernandes, S; Borges, J; Marques, R; Silva, C; Miguel, C; Cardoso, A; Trinca, R; Faustino, A
Abstract : Background: PROs are especially useful in the management of rheumatic diseases in complement to physician evaluation. However they are time consuming and used in a limited manner in the daily clinical practice. Reuma.pt is the Portuguese national rheumatic diseases register and one of the few registries in Europe that allows the patient to do at home the PROs before the appointment. In our institute we have complemented that with the creation of a paper free day hospital with the use of touch screen computers that also allows the patient to do the PROs before the clinical evaluation by the rheumatologist. Objectives: to compare the impact of the use off Reuma.pt at home PROs completion platform before and after the utilization of touch screen computers in the day hospital. Methods: We determined the number of patients and appointments with the use at home of the PROs platform one year prior to the introduction of the touch screen computer at our day hospital (October 2014 –October 2015) and one year after the paper free day hospital was installed (November 2015-November 2016). To determine any change of pattern of the use at home of the platform and the relations between that and patients characteristics. Results: When we analyse the available variables between the patients that performed the PROs at home we found for both periods considered that they were younger (45, 2/49, 8 vs 53, 4/55, 1 p<0.001) they have more education (11.8/10.35 vs 8.2/ 7, 9) no differences were found regarding gender. There is a tendency that with the continuous use of touchscreen computers at the day hospital less educated (T0 -11.8, T1–10.35 school years) and older patients (T0- 45, 2/ T1 -49, 8 years) are using more at home platform of Reuma.pt. Conclusions: The use of technology could have a consider impact on the way we collected data from our patients. With the use of a touchscreen computer we have improved not only the overall completion of PROs but also increased the familiarity of patient to the online questionnaires. Number of appoitments with previous at home completion of the questionnaires more than double. This has a clear impact on patient participation, quality of data in the registry but even more impact on time and human resources at a day hospital. Disclosure of Interest: None declared